Mapping Culture in the Waterloo Region: Exploring Dispersed Cultural Communities and Clustered Cultural Scenes in a Medium-sized City Region - Deveau, Danielle J.; Goodrum, Abby (Culture and Local Governance / Culture et gouvernance locale, 2015)
Currently undergoing rapid growth due primarily to a thriving tech sector, the Waterloo Region is increasingly concerned with the attraction and retention of key labour talent. Aspects of the creative economy, such as vibrant cultural scenes, nightlife, public spaces, and leisure amenities have been specifically identified by key stakeholders as vital to the continued growth and success of the region. While creative people certainly live and work in the Waterloo Region, labour shortages linked to challenges of worker attraction and retention indicate that the current talent base is not sufficient to meet regional economic needs. In this article, we engage critically with creative economy typologies which have been taken up in local cultural planning and explore some of the gaps and oversights that such ‘one-size-fits-all’ creative city models have in medium-sized post-industrial urban centres. Analyzed through the lens of cultural mapping methodologies, the region offers a valuable case study as it works to rebrand itself, altering its cultural fortunes through concerted city-building efforts.